Comparison of electronic compensation techniques in access networks with optical phase modulation and coherent detection (2017)
(Eng) QPSK modulation format with electronic compensation is an alternative to increase the capacity and reach in the next generation passive optical networks (NG-PON), in response to demanding services and applications. We perform simulations to compare the performance of two electronic compensation techniques Constant Modulus Algorithm (CMA) and Backpropagation, in a NG-PON with QPSK modulation and coherent detection for the compensation of the chromatic dispersion. We use CMA in the access network to increase the data bit rate up to 40 Gb/s and the reach up to 33.5 km, reducing the computational requirements compared with Backpropagation.